Population attributable fractions of modifiable dementia risk factors for cognitive impairment—the ELSA-Brasil cohort studyResearch in context - Raphael Machado Castilhos; Vanessa Bielefeldt Leotti; Natan Feter; Alessandra C. Goulart; André Russowsky Brunoni; Claudia Kimie Suemoto; Luana Giatti; Maria Carmen Viana; Sandhi Maria Barreto; Sheila Alvim; Bruce B. Duncan; Maria Inês Schmidt (The Lancet Regional Health. Americas, 2025)
Summary: Background: Population attributable fractions (PAF) of modifiable dementia risk factors are rarely estimated in low- and middle-income countries. We aim to estimate the relative risk (RR) for cognitive impairment and calculate the PAF in the Estudo Longitudinal da Saúde do Adulto (ELSA-Brasil). Methods: We analyzed adults aged 35–74 at the baseline (2008–2010) and wave 3 (2017–2019). We estimated the prevalence of eight modifiable dementia risk factors at baseline: hypertension, physical inactivity, diabetes, depression, obesity, low education, smoking, and excessive alcohol consumption. Cognition was evaluated at baseline and wave 3 using six standardized tests for the Brazilian Portuguese. A global cognitive score from the individual cognitive tests was created using calculated z-scores each test. A global z-score below −1.5 was considered indicative of cognitive impairment. We calculated the RR and PAF for cognitive impairment at wave 3. Findings: We followed 10,058 adults (56.7% women, median age of 50 [IQR: 44–56] years) for 8.1 (0.6) years. The eight-year incidence of cognitive impairment in wave 3 was 5.5% (n = 549). Low education had the largest RR (4.32) followed by hypertension (1.43), diabetes (1.27), and smoking (1.35). Low education had the largest PAF (95% CI), 14.2% (11.2–17.3), followed by hypertension 13% (7–19), diabetes 4.2% (0.7–7.7), and smoking 3.2% (0.45–6). The total PAF for significant risk factors was 34.7% (28.2–41.3). Interpretation: The findings highlight the importance of early-life and midlife prevention strategies in low- and middle-income countries, with a focus on addressing educational and cardiovascular risk factors. Funding: RMC received Alzheimer's Association grant (AARGD-21-846545).